2019
DOI: 10.1039/c9ra06146k
|View full text |Cite
|
Sign up to set email alerts
|

Screening of molecular targets and construction of a ceRNA network for oxaliplatin resistance in colorectal cancer

Abstract: Oxaliplatin resistance reduces the efficacy of chemotherapy for colorectal cancer (CRC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Previous studies demonstrated that HOTAIR enhanced the resistance of colorectal cancer to oxaliplatin 15–17 . To our knowledge, for the first time our evidence demonstrated that HOTAIR contributed to the resistance of GC to oxaliplatin dependent on ABCG2.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies demonstrated that HOTAIR enhanced the resistance of colorectal cancer to oxaliplatin 15–17 . To our knowledge, for the first time our evidence demonstrated that HOTAIR contributed to the resistance of GC to oxaliplatin dependent on ABCG2.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies demonstrated that HOTAIR enhanced the resistance of colorectal cancer to oxaliplatin. [15][16][17] To our knowledge, for the first time our evidence demonstrated that HOTAIR contributed to the resistance of GC to oxaliplatin dependent on ABCG2. These evidences indicated that HOTAIR could be a promising target for personalization chemotherapy for GC in future.…”
Section: Discussionmentioning
confidence: 60%
“…Specifically, the ceRNA network developed by the authors contained 503 lncRNA-miRNA-mRNA regulatory, 210 lncRNA-miRNA pairs, 382 miRNA-mRNA, and 212 mRNA co-expression pairs. Among these, HOTAIR and 14 mRNAs significantly correlated with patient prognosis for oxaliplatin resistance ( Wei et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNA are involved in important life processes such as cell proliferation and apoptosis, gene expression regulation, and individual development [14]. miRNA is closely related to tumorigenesis, development, and resistance to chemotherapy [15]. MiR-503-3p is a newly discovered mi RNA that is involved in the proliferation of certain tumors [16].…”
Section: Introductionmentioning
confidence: 99%